2006
DOI: 10.1182/blood-2005-11-013672
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma cell survival relies on high activity of protein kinase CK2

Abstract: Casein kinase 2 (CK2) is a ubiquitous cellular serine-threonine kinase that regulates relevant biologic processes, many of which are dysregulated in malignant plasma cells. Here we investigated its role in multiple myeloma (MM). Analysis of MM cell lines and highly purified malignant plasma cells in patients with MM revealed higher protein and CK2 activity levels than in controls (normal in vitro-generated polyclonal plasma cells and B lymphocytes). The inhibition of CK2 with specific synthetic compounds or by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 62 publications
(83 reference statements)
9
116
0
Order By: Relevance
“…Experimental transgenic mouse models of neoplasia in which altered CK2 signal served as a double transgene have provided significant support to this notion (e.g., Kelliher et al, 1996;Xu et al, 1999). The presence of elevated CK2 in cancer appears to correlate with the pathological status of the cancer and may serve as a prognostic marker (Yenice et al, 1994;Gapany et al, 1995;Faust et al, 1996;Faust et al, 1999;Piazza et al, 2006;Laramas et al, 2007). Although CK2 is present ubiquitously in all cells, it is noteworthy that its distribution in the normal versus cancer cells is distinct.…”
Section: Ck2 and Cancermentioning
confidence: 92%
“…Experimental transgenic mouse models of neoplasia in which altered CK2 signal served as a double transgene have provided significant support to this notion (e.g., Kelliher et al, 1996;Xu et al, 1999). The presence of elevated CK2 in cancer appears to correlate with the pathological status of the cancer and may serve as a prognostic marker (Yenice et al, 1994;Gapany et al, 1995;Faust et al, 1996;Faust et al, 1999;Piazza et al, 2006;Laramas et al, 2007). Although CK2 is present ubiquitously in all cells, it is noteworthy that its distribution in the normal versus cancer cells is distinct.…”
Section: Ck2 and Cancermentioning
confidence: 92%
“…46 CK2 in MM CK2 has also been implicated in the pathogenesis of MM. 47 Our group described that CK2 is crucial for malignant plasma cell survival demonstrating that this protein kinase positively regulates STAT3 and NF-kB-dependent signaling. CK2 activity and CK2a and b protein levels were found upregulated in MM cell lines and primary cells.…”
Section: Ck2 In Lymphoid Tumors Mouse Modelsmentioning
confidence: 99%
“…Similarly, we demonstrated that CK2 inhibition caused a reduction in STAT3 phospho-Tyr705 and phospho-Ser727 levels, implying this kinase as a positive regulator of two critical pro-survival pathways in MM. 47 Moreover, CK2 could be instrumental for the modulation of MM cell sensitivity to novel therapeutic agents. A recent study has reported that CK2 could represent a central kinase downstream inhibition of the proteasome with bortezomib, thus influencing the cell phosphoproteome and many signaling pathways upon treatment with this central, widely employed therapeutic agent.…”
Section: Ck2 In Lymphoid Tumors Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These kinases are, to the best of our knowledge, not known to contribute to BAD phosphorylation. The alpha isoforms of Casein kinase I (CK1, CSNK1) 16 and II (CK2, CSNK2) 17 have been implicated in contributing to multiple myeloma pathology, although the relevance of CK1 and CK2 in the setting of Pim overexpression is not known. Therefore, we believe off-target kinase inhibition to be a limited risk in the interpretation of the impact of 9c on BAD phosphorylation, but activity on CK1α/ CK2α may impact the viability of KMS-12-BM.…”
mentioning
confidence: 99%